ADSORPSI LOGAM Cu (II) MENGGUNAKAN KITOSAN DARI KULIT KERANG HIJAU - Kesumawati; Husni Husin; Muhammad Zaki2 (Politeknik Aceh, 2017)
Chitosan is a modification of chitin contained in the shell of green mussel which is cationic and biodegradable in the environment. The green mussel shell waste has some great potential benefits because it contains chitin which can be used as the main ingredient for chitosan production for Cu metal adsorption (II). The adsorption was by varying concentration and contact time. The adsorption analysis on the metal content of Cu was done by using the Atomic Adsorption Spectrophotometer (AAS) of Shidmazu type AA 6300 made in Japan. Parameter obtained in this study are adsorption capacity and absorption efficiency of metal Cu (II). Value of adsorption capacity and adsorption efficiency concentration of 5 mg/L are 4,835 mg/g and 96,72 %. The adsorption follows Freundlich absorption isotherm with R2of 0,906 and Freundlich constant (Kf) of 3,3118 l/g and l/n of 0,361. The adsorption of 5 mg/L concentration follows the pseudo second-order kinetics model with kinetics constant (k2) of 0,687 mg/g/min.